Reshape the Fates of Treg and CD8+T Cells Through IL‐2Rα by Synergizing Divergent Receptor‐Biased IL‐2 PEGylates - Jiaqi Sun; Lingfeng Guo; Dezhong Ji; Mengfan Yu; Boyang Cheng; Xingxing Zhu; Yeshuang Yuan; Siyu Wu; Yuanjie Zhang; Wen Shi; Zhiqian Chen; Xindang Chu; et al. (Advanced Science)
Abstract Clinical trials of receptor‐biased interleukin‐2 (IL‐2) variants in cancer therapy show limited efficacy. To investigate, we re‐evaluated divergent receptor‐biased IL‐2 PEGylates (generated via site‐specific PEGylation at residues D20 (not‐β) and Y45 (not‐α)), alone or in combination. Results showed the not‐α variant (Y45) activates regulatory T cells (Tregs) via βγ chain binding, overriding CD8+ T cells and impairing efficacy. Conversely, the not‐β IL‐2 (D20) is inert alone but spatially blocks Y45’s βγ engagement, suppressing Treg activation. D20 also modulates activated CD8+ T cells by preferentially binding the α chain, disrupting Y45‐mediated βγ signaling to prevent exhaustion and terminal differentiation. Synergy between these PEGylates highlights the α chain as a regulatory switch reshaping Treg, CD8+ T cell, and endothelial cell fates. In syngeneic tumor models, combined therapy enhanced CD8+ T cell infiltration, suppressed tumor growth, and reduced vascular leak syndrome risk. These findings propose combinatorial IL‐2 strategies targeting α chain regulation to optimize antitumor responses.